“To telle yow [. . .] whiche they weren, and of what degree”: direct characterization across the centuries - Landert, Daniela (Narrative, 2025)
This contribution studies how characterization - the way in which characters are presented to readers - has changed between the Late Middle English period and the twenty-first century. Investigating a small sample of texts from four different periods, I compare the type of information that is provided about the protagonists of the texts when they are first introduced to the reader. The study is situated within the field of pragmatics of fiction and it presents a method with which characterization can be compared systematically across different texts, even diachronically. The results of the study show that there have been marked changes over time with respect to which categories of character information are mentioned explicitly, but also about how certain categories are used. These shifts reflect socio-cultural changes, for instance with respect to the role of the family for individual identity. The results demonstrate that studying characterization diachronically can reveal insight about the links between linguistic style, literary conventions, and broader social and cultural developments that shape literary texts.
Gesehen am 12.05.2025